2019
DOI: 10.14453/aabfj.v13i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Listening Skills: Accountancy Educators in Retreat?

Abstract: This study aims to explore the financial and governance factors that determine related party transactions (RPTs) in the developing country context of Jordan.. To do so, a multiple regression model was developed and used. Results show that RPTs are negatively related with CEO-duality and board independence, while they are positively related with firm leverage, ownership concentration, board size, and audit quality. However, no statistically significant relation was found between RPTs and firm profitability or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 65 publications
(109 reference statements)
0
11
0
Order By: Relevance
“…monitoring role of the independent directors in controlling the payments to the related parties. The significantly negative relationship between the board independence and RPTs is supported by the findings of Gordon et al, 2004;Kohlbeck and Mayhew 2004;Azim et al, 2018;Gallery, Gallery and Supranowicz;2008, Abdullatif et al,2019. On the contrary, other empirical studies have found a positive relationship between the independence of board of directors and RPTs such as Sharkar et al, 2007, Chen et al, 2014, Wu and Li, 2015, Zhu et al, 2016, Boateng and Huang, 2017, and Reguera-Alvarado and Bravo, 2017.…”
Section: The Board Independencementioning
confidence: 81%
See 3 more Smart Citations
“…monitoring role of the independent directors in controlling the payments to the related parties. The significantly negative relationship between the board independence and RPTs is supported by the findings of Gordon et al, 2004;Kohlbeck and Mayhew 2004;Azim et al, 2018;Gallery, Gallery and Supranowicz;2008, Abdullatif et al,2019. On the contrary, other empirical studies have found a positive relationship between the independence of board of directors and RPTs such as Sharkar et al, 2007, Chen et al, 2014, Wu and Li, 2015, Zhu et al, 2016, Boateng and Huang, 2017, and Reguera-Alvarado and Bravo, 2017.…”
Section: The Board Independencementioning
confidence: 81%
“…Empirical studies have generally found a positive relation between the RPTs and the firm's leverage such as Nekhili & Cherif, 2011, and Utama & Utama, 2014, Abdullatif, et al, 2019 and this is reasonable because firms with high leverage is most likely to engage into RPTs to overcome this. In this research, we expect that the firm's leverage is to be positively related to the RPTs of firms in Egypt.…”
Section: -2-1 Firm's Leveragementioning
confidence: 94%
See 2 more Smart Citations
“…These are the primary research questions addressed by the papers published in this issue of AABFJ. Abdullatif, Alhadab and Mansour (2019) investigated the relationship between various financial and governance factors and related party transactions of Jordanian companies. Research on related party transactions is exhaustively done.…”
mentioning
confidence: 99%